Effects of disturbed electric fields in the low‐latitude and equatorial ionosphere during the 2015 St. Patrick's Day storm - Kuai, Jiawei (2016)
The 2015 St. Patrick's Day geomagnetic storm with SYM‐H value of −233 nT is an extreme space weather event in the current 24th solar cycle. In this work, we investigated the main mechanisms of the profound ionospheric disturbances over equatorial and low latitudes in the Asian‐Australian sector and the American sector during this super storm event. The results reveal that the disturbed electric fields, which comprise penetration electric fields (PEFs) and disturbance dynamo electric fields (DDEFs), play a decisive role in the ionospheric storm effects in low latitude and equatorial regions. PEFs occur on 17 March in both the American sector and the Asian‐Australian sector. The effects of DDEFs are also remarkable in the two longitudinal sectors. Both the DDEFs and PEFs show the notable local time dependence, which causes the sector differences in the characteristics of the disturbed electric fields. This differences would further lead to the sector differences in the low‐latitude ionospheric response during this storm. The negative storm effects caused by the long‐duration DDEFs are intense over the Asian‐Australian sector, while the repeated elevations of hmF2 and the equatorial ionization anomaly intensifications caused by the multiple strong PEFs are more distinctive over the American sector. Especially, the storm time F3 layer features are caught on 17 March in the American equatorial region, proving the effects of the multiple strong eastward PEFs.